GENDER AND OTHER SIGNIFICANT FACTORS CAUSING DISPARITIES IN SENIOR HIGH SCHOOL STUDENTS’ MATHEMATICS PERFORMANCE - Amoah, Emmanuel (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Research findings on gender and other student related, teacher related and school related factors affecting students’ performance in mathematics are still debatable. With the recent trend of poor performance in mathematics recorded in both district and national performance statistics in the Assin North District, this present study examined gender factor and other significant factors causing disparities in mathematics performance among high school students. A mathematics achievement test and questionnaires were employed to collect data from a representative sample of 500 final-year students from three public senior high schools in the Assin North District, Ghana. Data were analysed descriptively and quantitatively using independent t-test and probit regression. Results show that male students did better than female students in the mathematics achievement test. The differences were statistically significant at .05 significance level. Aside gender, self-assurance and self-regard were identified as significant student related factors affecting the mathematics performance among senior high school students in the Assin North District. Teacher subject matter knowledge, teacher methods and teacher-student interaction were also significant teacher related factors affecting performance in mathematics. Finally, teacher motivation and school environment were identified as significant school related factors affecting mathematics performance among the senior high school. Other factors such as students’ socioeconomic background and teaching resources had effect on students’ performance but they were not statistically significant. The study recommends that senior high school mathematics teachers should employ gender responsive pedagogies in their teaching practices. It is also recommended that professional learning communities should also be formed at school levels to enable mathematics teachers improve upon their knowledge, motivation and teaching styles.